Transnational Drug Trafficking: Studi Kasus Peningkatan Peredaran Narkotika di Bangladesh - Ramadhan, Bayu Arif; Achsin, Muhaimin Zulhair (Department of International Relations, Brawijaya University, 2020)
Drug trafficking is one of the numerous acts of transnational criminal organizations (TOC). Bangladesh upon the course of 2015- 2017, had suffered from the intense drug flow, especially from the type of Yaba/amphetamine-type stimulant (ATS) in which peaked itself in 2015 by 211,2% percentage comparing to the previous years according to Drug Narcotics Control (DNC) reports and various media outlets. These flows were suspiciously running from the neighborhood country from Bangladesh, Myanmar, due to the unavailability of domestic yaba/ATS producers within Bangladesh. Contradict to the prevailing course of domestic anti-drug law in Bangladesh as embodied within the Drug Narcotics Act 2002, which tries to curb and prohibit whole activities regarding drug trafficking or flow. Therefore the writer was curious to conduct further research to examine the factors available to influence the intensity of drug trafficking and flow in Bangladesh upon 2015-2017.